A literature review of the impact of HIV and AIDS on the role of the elderly in the sub-Saharan African community - Eucebious Lekalakala- Mokgele (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2011)
The status of older adults in Africa occupies a small but rapidly expanding share of the global literature on ageing. The human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) pandemic has generated a new focus on the changing role of the elderly in communities that have been affected. In sub-Saharan Africa, where millions are projected to be infected with HIV and about two million deaths are recorded annually amongst the traditionally productive adults, such loss of parents and breadwinners means children and the elderly have had to take up unusual responsibilities. A literature review on the elderly and HIV and AIDS provided the data analysed for this article. Access to databases was mainly via EBSCO (www.ebsco.co), which allowed searches in major databases and search engines useful in an academic setting for finding and accessing articles in health and health-related academic journals, repositories and archived reports. Results showed that the AIDS pandemic has direct and indirect effects which have manifested in a set of interrelated social, economic and psychological dimensions that could ultimately impact on the health and well-being of the elderly. It is concluded that more needs to be done to articulate the knowledge base of the impact of HIV and AIDS in order to inform social, economic and political policies for the purpose of alleviating the problems that the pandemic is wreaking on the elderly African population. Opsomming